Promoting Green Buildings and Low-Carbon Design Strategies of Green B&B Rooms for Sustainable Tourism after COVID-19 - Gangwei Cai; Min Zhang; Xiandu Zhang; Huijian Xi; Zhong Chen; Chao Liu; Kang Liu; Ke Liu; Shiwen Xu; Zuoping Yu (Land, 2023)
COVID-19 opened a window of opportunity to change the green development of the hospitality industry. For many years, Chinese tourists have been the world’s largest source of outbound tourists. Therefore, this study attempted to improve built-environment strategies for green rooms at B&Bs using the empirical statistics of Chinese tourists after the end of COVID-19 control measures and different green B&B standards, combining IPA (importance-performance analysis). For the lack of a green built-environment study from a tourism perspective, this study can be used mainly for improving the green satisfaction of urban B&Bs as it attempted to fill the gaps in research on green B&B rooms. This study will significantly help improve the quality of green rooms for the B&B industry in the future, and it also provides an improved green B&B room sample for other countries and regions. Moreover, it is an optimistic attempt at hospitality and tourism recovery.